Synthesis of BiOCl Nanosheets by a Simple Ultrasonic Route - Guan, Hangmin (Asian Journal of Chemistry, 2014)
Ternary bismuth oxyhalide (BiOX, X = F, Cl, Br, I) with layered structure have emerged as promising photocatalysts for water splitting and environmental remediation. Ultrathin BiOCl nanosheets were achieved by a simple ultrasound way. The product was characterized by XRD, SEM and TEM.